Ethnobotany in Rayones, Nuevo León, México - Estrada Castillón, Andrés Eduardo; Garza López, Miriam; Villarreal Quintanilla, José Ángel; Salinas Rodríguez, María Magdalena; Soto Mata, Brianda Elizabeth; González Rodríguez, Humberto; González Uribe, Dino Ulises; Cantú Silva, Israel; Carrillo Parra, Artemio; Cantú Ayala, César (Springer Nature, 2014)
Trough collections of plants and interviews with 110 individuals, an ethnobotanical study was conducted in order to determine the knowledge and use plant species in Rayones, Nuevo Leon, Mexico. The aim of this study was to record all useful plants and their uses, to know whether differences exist in the knowledge about the number of species and uses between women and men, and to know if there is a correlation between the age of individuals and knowledge of species and their uses.